PECULIARITIES OF APPLICATION OF PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS IN ADMINISTERING OF JUSTICE IN UKRAINE - Толкачова, Ірина Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: practice of the European Court of Human Rights and peculiarities of its application in administering of justice in Ukraine are researched in the article. Methods of research: there were used the following methods during writing of the article: philosophical, general scientific and special. Results: activity of the European Court of Human Rights, its role and influence on the judicial system of Ukraine were analyzed, appropriate examples were given. Discussion: observance and use in Ukraine of the Convention for the Protection of Human Rights and Fundamental Freedoms.